The Allure of the Exotic: Reexamining the Use of Local and Distant Pipestone Quarries in Ohio Hopewell Pipe Caches. Issue 1 (20th January 2013) - Emerson, Thomas E.; Farnsworth, Kenneth B.; Wisseman, Sarah U.; Hughes, Randall E.
Abstract: Mary W. Helms's observation that spatial distance often correlates with spiritual power has become an axiom in interpreting the role of exotic materials in societies. This is especially evident in explanations of the North American Hopewell Interaction Sphere. The circulation and accumulation of exotic materials in massive mortuary caches peaked during the Hopewell era (100 B.C. to A.D. 300). The premise that Hopewell smoking pipes were made in Ohio, primarily of local raw material, and circulated to foreign locations was an integral part of this interaction model. In this study we demonstrate, primarily using reflectance near-infrared spectroscopy (NIS), that early Hopewell Tremper Mound pipe raw-material acquisition focused on exotic pipestones from Illinois and Minnesota. By contrast, later Mound City cache pipes were almost exclusively made from local limestone and pipestone. The discovery of this shift in preference for and/or access to different quarry sources by Ohio Hopewell societies provides new perspectives on early Hopewell development and long-distance interaction.